The impact of COVID-19 outbreak towards the post-pandemic leisure travel intention/ Angela Susanto ... [et al.] - Susanto, Angela; Amelia, Ayu; Amadea, Catherine; Hendriana, Evelyn (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
There are studies related to COVID-19 pandemic across various sectors, including social, psychology, and specific industries, e.g., tourism. Several countries have imposed travel restrictions to prevent COVID-19 outbreaks and it may lead to travel behaviour changes for their residents. This research contributes to the existing knowledge by providing a new point of view, by extending the Theory of Planned Behaviour (TPB) along with additional determinants of travellers’ post-pandemic behavioural intentions, namely cognitive and affective risk perception and non-pharmaceutical interventions. This study focused on Indonesian residents who intended to travel abroad for vacation in 2020, but their plan was postponed due to the COVID-19 pandemic. Data was collected using a convenience sampling technique and analysed using partial least squares structural equation modelling (PLS-SEM). The PLS-SEM enables us to predict the key factors that affect postpandemic travel intentions. The results show that affective risk perception has a positive relationship with perceived behavioural control and non-pharmaceutical intervention. This research also found significant effects of cognitive risk perception on all variables. Positive significant relationships were found between attitude, subjective norms, perceived behavioural control, and non-pharmaceutical interventions with post-pandemic travel intentions.